(3GdWH GdQhMGfjs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3bGd CHh HcQ eMeO Hf RcQjG GdQGRj , GdBQGA aj GdeONd Edi GdadSaI KdGKI s
(3BNQgG (B:s
(3hEP bO CJjfG Ydi bUOfG ajeG CdafG ajg cJGHfG gPG hHdZfG aEfG NGJehf cdGefG HGdTcQ ddg Ld KfGDg YR hLd , hgh MSHfG hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdWH (B- (3U (B27 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B148 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs